110kV Lightning-proof and Ice-proof Insulators and Explosion-proof Research. Issue 1 (June 2020) - Peng, Yongjing; Fang, Zhen; Wang, Bowen; Hu, Jianping; Wu, Wei
Abstract: At present, the transmission line realizes the effect of lightning protection and supporting wires by connecting insulators and lightning arresters in parallel. However, due to the large weight and volume of lightning arresters, the space of the cross arm of the iron tower is limited, the workload of lightning arresters installation and line operation and maintenance is greatly increased, and the live operation is more difficult. Aiming at the problems that lightning arresters do not have the ability to hang wires, and additional hanging points are needed during installation, and the cross arm of iron tower is reformed, this paper proposes a lightning protection composite insulator combining lightning arresters and insulators. In view of the anti-explosion performance of lightning arresters, the existing research mostly focuses on the discussion and theoretical analysis of lightning arresters explosion accidents, and seldom involves the anti-explosion performance test of lightning arresters. In this paper, the practicability and reliability of the 110kV lightning-proof and ice-proof insulator are illustrated through the explosion-proof performance test and mechanical performance test of the proposed 110kV lightning-proof and ice-proof insulator.